Characteristics of persons who inject drugs and who witness opioid overdoses in Vietnam: a cross-sectional analysis to inform future overdose prevention programs - Blackburn, N.A. (Harm Reduct J, 2017)
BACKGROUND: Persons who use opioids have a high risk of overdose and associated mortality. In Vietnam, little is known about the characteristics of this population and the persons who are witness to those overdoses. One approach to combatting fatal overdose has been the use of peer interventions in which a friend or injecting partner administers overdose reversal medication, but availability in Vietnam of these medications is limited to pilot programs with aims to expand in the future (Le Minh and V.F. Go, Personal Communication, 2016). The primary objective of this paper is to explore the characteristics associated with witnessing three or more overdoses in a lifetime. METHODS: This cross-sectional analysis used baseline data from a four-arm randomized control trial conducted in Thai Nguyen, Vietnam, known as the Prevention for Positives project. One thousand six hundred seventy-three PWID were included in the analysis. We conducted bivariable and multivariable logistic regression to identify characteristics associated with witnessing three or more overdoses in a lifetime. Characteristics explored included education, employment, marital status, risky drug use behaviors, locations for accessing syringes, recent overdose, history of incarceration, drug treatment, and having slept outside in the past 3 months. RESULTS: Seventy-two percent (n = 1203) of participants had witnessed at least one overdose in their lifetime, and 46% had witnessed three or more overdoses (n = 765). In the multivariable model, having less than secondary education (AOR 0.70; 95% CI 0.57, 0.86), having slept outside in the past 3 months (AOR 1.77; 95% CI 1.31, 2.40), having a history of incarceration (AOR 1.33; 95% CI 1.07, 1.65), having a history of drug treatment (AOR 1.41; 95% CI 1.12, 1.77), experiencing a recent non-fatal overdose (AOR 3.84; 95% CI 2.36, 6.25), injecting drugs daily (AOR 1.79; 95% CI 1.45, 2.20), receptive needle sharing (AOR 1.30; 95% CI 1.04, 1.63), and number of years injecting (AOR 1.04; 95% CI 1.02, 1.07) were significantly associated with witnessing three or more overdoses. CONCLUSIONS: Targeted interventions are needed to train persons witnessing an overdose to administer overdose-reversal medication. This includes targeting persons prior to release from prisons, drug treatment centers, and those accessing syringe exchange programs. Additional research should assess the burden of witnessing an overdose as well as locations for medication distribution. Assessments of the training capacity and needs for implementing these programs among drug using peers in Vietnam are of the utmost importance.